KINERJA PANEL INSULASI BERBAHAN LIMBAH SELULOSA DALAM MENGURANGI SUHU RUANGAN (Jurnal Arsitektur ARCADE, 2026)
Global warming has increased indoor temperatures in buildings, particularly in tropical climate regions. This study aimed to evaluate the thermal performance of composite insulation panels made from cellulose-based waste materials, namely newspaper, cardboard, and sawdust, using polyvinyl acetate (PVAc) and tapioca starch as binders, in reducing indoor temperatures. A comparative experiment was conducted using four test boxes measuring 240 mm × 220 mm × 340 mm, made of 9 mm thick calcium silicate board, with one side wall replaced by a metal sheet oriented toward the west. The air temperature inside the test boxes was continuously measured using a data logger during the peak heat load period from 12:00 to 16:00 Western Indonesian Time (WIB). The results showed that all tested panels reduced indoor temperatures compared with the control box without insulation. The newspaper-based panel bonded with PVAc exhibited the best thermal performance, with an average temperature reduction of 1.2 °C and a peak temperature reduction of 1.9 °C. In contrast, using tapioca starch as a binder with cardboard resulted in the lowest temperature reduction. These findings indicate that composite panels made from cellulose-based waste have potential as alternative thermal insulation materials for mitigating indoor temperature increases in tropical climates.